Methanolysis of Ceiba Petandra (Kapok) seed for high yield fatty acid methyl ester (FAME): A parametric study - Indah Thuraya, Herman; Faridah, Mukhrofun; Khairuddin, Md Isa; Naimah, Ibrahim; Mohd Aizudin, Abd Aziz (IOP Publishing Ltd, 2021)
The feedstock that has high potential for biodiesel production was investigated. The ceiba petandra (CP) seed was used in this study as the feedstock. The methanolysis of the CP seed to produce high yield of Fatty Acid Methyl Ester (FAME) was studied. Hydrothermal liquefaction (HTL) was used to produce the bio-crude from the CP with high ester yield. The gas chromatography- mass spectrometry was used to analyze the chemical content in the bio-crude. The highest oil yield was 44.68% which was obtained at 60 minutes reaction time, 300oC temperature and 4:1 methanol/ oil mass ratio. The optimum parameters for the highest ester content (67.33%) was obtained at 60 minutes reaction time, 300 oC temperature and 3:1 methanol/oil mass ratio. It is observed that CP seed has potential for the production of biodiesel.